Pengaruh Pendekatan Teacher Centered Learning terhadap Hasil Belajar Matematika Siswa Kelas III SDN 3 Balaesang Tanjung - Ni Komang hasari; Sukri; Moh Idil; Wa Ode Rizka Amaluddin; Eka Afrianda (JURNAL DIKDAS, 2026)
This study aims to determine the effect of the Teacher Centered Learning approach on the mathematics learning outcomes of third-grade students at SDN 3 Balaesang Tanjung. This research used a quantitative approach with a descriptive method. The subjects of this study were 14 third-grade students of SDN 3 Balaesang Tanjung. The data collection techniques used in this research were observation, interviews, and documentation. The students’ learning outcome data were obtained from mathematics evaluation scores and analyzed using descriptive statistical analysis by comparing students’ scores with the Minimum Mastery Criteria (KKM) set at 75. The results showed that out of 14 students, 9 students achieved learning mastery while 5 students did not achieve mastery. The percentage of students who achieved learning mastery was 64%, while 36% of students had not yet achieved mastery. These results indicate that the Teacher Centered Learning approach can help students understand mathematics learning materials, although there are still several students who have not achieved learning mastery.